International Responses to Human Rights Violations in Myanmar: The Case of the Rohingya (Journal of International Studies, 2020)
While Myanmar is a multi-ethnic and multi-religious country, the Bamar (Burmese) nonetheless comprise almost 70 percent of the country’s total population. Of the many ethnic groups in Myanmar, the Muslim Rohingya, are mainly centered in the Rakhine (Arakan) State, which borders Bangladesh. Although the position of these people as a distinct ethnic group was recognized by the U Nu government (1948-1962), the introduction of the 1982 Citizenship Act by the country’s military government, however, have rendered them stateless. Subject to a wide range of systematic human rights violations by the Myanmar authorities, the Rohingya have often sought refugee in Bangladesh as well as many other countries in the region and beyond. Whilst most like-minded states and international organizations have duly responded to the issue, especially by providing humanitarian assistance and criticizing the Myanmar junta for its treatment of the Rohingya, however, much remains to be done to find a permanent solution to the issue of statelessness of these people. The purpose of this article is therefore to analyze responses from some segments of the international community over the issue of human rights violations on the Rohingya and the resulting exodus of these people from Myanmar. As such, this article will examine responses from Bangladesh, the Association of Southeast Asian Nations (ASEAN) and the regional community, the United States, the European Union (EU), the United Nations (UN) and the Organization of the Islamic Conference (OIC).